2022
DOI: 10.1080/21623945.2022.2085417
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and vitamin D modulate adipose-derived stem cell differentiation towards the beige phenotype

Abstract: Adipose-derived stem cells (ADSCs) represent an ideal stem cell population for regenerative medicine. ADSC adipogenic differentiation is controlled by the activation of a specific transcriptional program, including epigenetic factors and key adipogenic genes. Under certain conditioned media, ADSCs can differentiate into several phenotypes. We previously demonstrated that bioactive molecules could counteract lipid accumulation and regulate adipogenesis, acting on inflammation and vitamin D metabolism. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Additionally, Muzumdar et al conducted an in vivo study on 101 rats to investigate the role of central and peripheral HN on insulin action. It was demonstrated that continuous intra-cerebro-ventricular infusion of HN significantly improved overall insulin sensitivity [ 29 , 97 ]. Activation of hypothalamic STAT-3 signaling was associated with central effects of HN on insulin action; such effects were canceled by co-inhibition of hypothalamic STAT-3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Muzumdar et al conducted an in vivo study on 101 rats to investigate the role of central and peripheral HN on insulin action. It was demonstrated that continuous intra-cerebro-ventricular infusion of HN significantly improved overall insulin sensitivity [ 29 , 97 ]. Activation of hypothalamic STAT-3 signaling was associated with central effects of HN on insulin action; such effects were canceled by co-inhibition of hypothalamic STAT-3.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors speculate that mitochondrial dysfunction may be beneficial to the cell because it may elicit an effective stress response [ 72 ]. Through these, mitochondria regulate not only energy production but a cellular homeostasis that includes a range of processes such as immune/inflammatory responses, proteostasis, adaptive responses to stress, and apoptosis [ 96 , 97 , 98 ]. Muscle humanin expression is upregulated in humans, in response to exercise stress, mtDNA mutation-associated diseases, and healthy aging, suggesting a tissue-specific response aimed at restoring mitochondrial homeostasis [ 102 ] in response to stress from, for example, acute exercise [ 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…When upregulated, miR-148a promotes adipogenic differentiation, 116 while it inhibits preadipocyte differentiation when miR-145 is upregulated and miR-148 117 is downregulated [51] (Figure 1). These molecules are also able to modulate inflammation 118 and the expression of other key genes involved in adipogenic differentiation, 119 counteracting WAT formation, and inducing a "brown-like" phenotype [52,53]. The use 120 of bioactive molecules and chemical stimuli can then control the de-novo lipogenesis, 121 differentiation, and physiology of adipose tissue, for the in vivo treatment of chronic 122 pathological conditions of difficult resolution.…”
Section: Epigenetic Programming Of Adipose-derived Stem Cells (Adscs)mentioning
confidence: 99%